Prevention of incisional hernia after midline laparotomy with prophylactic mesh reinforcement: a meta‐analysis and trial sequential analysis. Issue 3 (14th February 2020) - Jairam, A. P.; López‐Cano, M.; Garcia‐Alamino, J. M.; Pereira, J. A.; Timmermans, L.; Jeekel, J.; Lange, J.; Muysoms, F.
Abstract : Background: Incisional hernia is a frequent complication after abdominal surgery. The aim of this study was to assess the efficacy of prophylactic mesh reinforcement (PMR) after midline laparotomy in reducing the incidence of incisional hernia. Methods: A meta‐analysis was conducted following PRISMA guidelines. The primary outcome was the incidence of incisional hernia after follow‐up of at least 12 months. Secondary outcomes were postoperative complications. Only RCTs were included. A random‐effects model was used for the meta‐analysis, and trial sequential analysis was conducted. Results: Twelve RCTs were included, comprising 1815 patients. The incidence of incisional hernia was significantly lower after PMR compared with sutured closure (risk ratio (RR) 0·35, 95 per cent c.i. 0·21 to 0·57; P < 0·001). Both onlay (RR 0·26, 0·11 to 0·67; P = 0·005) and retromuscular (RR 0·28, 0·10 to 0·82; P = 0·02) PMR led to a significant reduction in the rate of incisional hernia. The occurrence of seroma was higher in patients who had onlay PMR (RR 2·23, 1·10 to 4·52; P = 0·03). PMR did not result in an increased rate of surgical‐site infection. Conclusion: PMR of a midline laparotomy using an onlay or retromuscular technique leads to a significant reduction in the rate of incisional hernia in high‐risk patients. Individual risk factors should be taken into account to select patients who will benefit most. [Correction added on 19 February 2020, after first online publication: J. García Alamino has been amended to J. M. Garcia‐Alamino] Abstract : Prophylactic mesh reinforcement of a midline laparotomy leads to a significant reduction in the rate of incisional hernia in high‐risk patients, for both onlay and retromuscular mesh reinforcement. Mesh high risk patients Abstract : Antecedentes: La eventración (hernia incisional) es una complicación frecuente de la cirugía abdominal. El objetivo es evaluar la eficacia de la inserción de una malla profiláctica de refuerzo ( prophylactic mesh reinforcement, PMR) después de la laparotomía media para reducir la incidencia de eventración. Métodos: Se realizó un metaanálisis siguiendo las recomendaciones PRISMA. La variable principal fue la incidencia de eventración después de un seguimiento mínimo de 12 meses. Las variables secundarias fueron las complicaciones postoperatorias. Solo se incluyeron ensayos controlados aleatorizados. Se utilizó un modelo de efectos aleatorios para el metaanálisis y se realizó un análisis secuencial de los ensayos. Resultados: Se incluyeron 12 ensayos aleatorizados y controlados con 1.815 pacientes. La incidencia de eventración fue significativamente menor después de la PMR en comparación con el cierre simple (riesgo relativo, RR 0, 35; i.c. del 95%: 0, 21‐0, 57, P < 0, 0001). Hubo una reducción significativa de la tasa de eventración tanto si la PMR se colocó en posición supra‐aponeurótica (RR 0, 26; i.c. del 95% 0, 11‐0, 67, P = 0, 005) como retromuscular (RR 0, 28; i.c. del 95% 0, 0‐0, 82, P = 0, 02). La aparición de seromas fue mayor en los pacientes con RPM supra‐aponeurótica (RR 2, 23; i.c. del 95% 1, 10‐4, 52, P = 0, 03). La PMR no conllevó una mayor tasa de infecciones de la herida quirúrgica. Conclusión: Una PMR en una laparotomía de la línea media, tanto en posición supra‐aponeurótica como retromuscular, reduce de forma significativa el desarrollo de eventraciones en pacientes de alto riesgo. Se deben considerar los factores de riesgo individuales para seleccionar a los pacientes que más puedan beneficiarse.